Prevalence of Suicidal Ideation and Allied Factors Among Patients with Depressive Disorder Visiting Psychiatry Outpatient Unit of Dessie Referral Hospital, South Wollo, Ethiopia - Prem Kumar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Suicide is the act of intentionally causing one's own death. It is a psychiatric emergency. Depressive disorder continues to be associated with an under-recognized risk for suicidal ideation. Suicidality in depressive disorder is not only a predictor of future attempted suicide and completed suicide; it is also associated with reducing the quality of life and people who die by suicide are frequently undiagnosed and untreated peoples with depressive disorder. Objective The aim of this study was to assess the prevalence and allied factors of suicidal ideation patients with depressive disorder at outpatient unit of Dessie Referral Hospital, South Wollo, Ethiopia. Methods An Institution based cross -sectional study was conducted. A systemic random sampling technique was used to get 423 patients from April to May 2015. Composite international diagnostic interview was used to collect data. Data entered in to EPI-INFO version 7 and transferred to SPSS version 20 for further analysis. Logistic regression was carried out and odds ratio with 95% confidence intervals was computed. Results The prevalence of suicidal ideation was found to be to 26.6%. Female sex [AOR=2, 95%CI: 1.04-2.88], Those who live alone [AOR=3.64, 95%CI:2.11-6.96], Family history of suicidal attempt [AOR=4.05, 95%CI: 2.49-6.58], and those who ever use substance [AOR=1.77, 95%CI: 1.07-2.91] were associated with suicidal ideation. Conclusion and recommendations Prevalence of suicidal ideation high among people with depressive disorders patients. In this study Sex, living alone, ever substance use and family history of suicidal attempt, were significantly associated with suicidal ideation. Effective strategies like; proper treatment of depressive disorder, strengthening social ties and prevention of psychoactive substance use have to be designed to prevent completed suicide among patients with depressive disorder.